2013
DOI: 10.1155/2013/656372
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Processing Method on the Mechanical and Electrical Properties of MWCNT/PET Composites

Abstract: Multiwalled carbon nanotube (MWCNT)/polyethylene terephthalate (PET) composites were prepared by three processing methods: direct extrusion (DE), melt compounding followed by extrusion (MCE), and dispersion of the MWCNTs in a solvent by sonication followed by extrusion (SSE). The mechanical properties of the MWCNT/PET composites processed by MCE increased with 0.1 wt% MWCNTs with respect to the neat PET. The electrical percolation threshold of MWCNT/PET composites processed by DE and MCE was ~1 wt% and the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…To illustrate, melt-compounded PET/MWCNT composites have shown higher tensile strength than pure PET, whereas composites made by other methods such as direct extrusion and solvent dispersion plus extrusion have not shown improvement in tensile strength (Rodríguez-Uicab et al, 2013). To illustrate, melt-compounded PET/MWCNT composites have shown higher tensile strength than pure PET, whereas composites made by other methods such as direct extrusion and solvent dispersion plus extrusion have not shown improvement in tensile strength (Rodríguez-Uicab et al, 2013).…”
Section: Mechanicalmentioning
confidence: 96%
See 3 more Smart Citations
“…To illustrate, melt-compounded PET/MWCNT composites have shown higher tensile strength than pure PET, whereas composites made by other methods such as direct extrusion and solvent dispersion plus extrusion have not shown improvement in tensile strength (Rodríguez-Uicab et al, 2013). To illustrate, melt-compounded PET/MWCNT composites have shown higher tensile strength than pure PET, whereas composites made by other methods such as direct extrusion and solvent dispersion plus extrusion have not shown improvement in tensile strength (Rodríguez-Uicab et al, 2013).…”
Section: Mechanicalmentioning
confidence: 96%
“…In comparative studies on PET/MWCNT composites made by different methods, it was shown that Raman spectral peaks of PET/MWCNT nanocomposites were almost identical to plain PET with one slight difference at wavenumber 1287 cm −1 where the CO bond of PET overlapped the 1331 cm −1 peak corresponding to the D band of MWCNT (Rodríguez-Uicab et al, 2013). In comparative studies on PET/MWCNT composites made by different methods, it was shown that Raman spectral peaks of PET/MWCNT nanocomposites were almost identical to plain PET with one slight difference at wavenumber 1287 cm −1 where the CO bond of PET overlapped the 1331 cm −1 peak corresponding to the D band of MWCNT (Rodríguez-Uicab et al, 2013).…”
Section: Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…PET is a low-cost, high-performance, semi-crystalline thermoplastic polymer that is used in the automobile and electronic industries and also has a variety of applications such as textiles, films, industrial fibers, bottle containers, and food packaging. [4,5] However, inadequate thermal stability and mechanical properties of PET have hindered its valuable application in a wide range of industry. [6] Carbon nanotubes (CNTs) are ideal candidates as reinforcements for thermoplastic polymer composites that can improve the electrical, mechanical, and thermal properties of the polymers.…”
Section: Introductionmentioning
confidence: 99%